DEVELOPING STUDENTS' READING ABILITY USING EXTENSIVE READING - Sumartono, Sumartono; Aflahatun, Nur; Cahyani, Intan Dwi (Jurnal Bahasa Inggris, 2019)
This study intends to find out the influent of students? reading ability through extensive reading and to find out the result of using various text in reading activities. This research using classroom action research. Consists of two cycles. Technique collecting data used in this research is a mixed-method (qualitative and quantitative). The technique of analyzing data used is descriptive analysis. The result of this research showed the development of students reading ability through extensive reading. Use two types of extensive reading, i.e., skimming and superficial. By using three-technique of extensive reading that is skipping, skimming and scanning. Extensive reading conducted in the first cycle and second cycle. Based on the research result from pre-cycle until post cycle, students? reading ability was increased 50,4 %.